Hoạt động tài trợ vốn cổ phần và hiệu ứng giá trị - Bằng chứng tại Việt Nam - Trần Thị Hải, Lý; Phan Vương, Nhật (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2017)
This paper investigates whether the source of value-growth returns is due to risk premium or misvaluation. The sample includes all non- financial companies listed on Hochiminh Stock Exchange (HOSE) and Hanoi Stock Exchange (HNX) during the period from July 2009 to June 2016. By examining the case at both portfolio and company levels, we find evidence that Vietnamese value-growth returns are strongly dependent on the valuation signals in firm's equity financing activities. In other words, firm's financing activities can magnify or reduce excess returns. When market expectation errors are taken into account, value firms with strong fundamentals are undervalued, whereas growth firms with weak fundamentals are overvalued. This result indicates that the large difference in the stock returns between value purchasers and growth issuers cannot be explained by common risk factors, but can be partly attributed to mispricing
Keywords: Value stock; Growth stock; Stock issues; Stock repurchases; Risk premium